(untitled) (Medicine Today, 2017)
A descriptive type of cross sectional study was carried out to assess the pattern of infant & young child feeding practices by the rural mothers of Bangladesh with a sample size of 450 during the months of January, 2015 to December, 2015. Out of 450 children, 51.1% are female & 48.9% are male. The proportions of infants with early initiation of breastfeeding (13.6%) and exclusive breastfeeding fewer than six months (57.3%) and infants who received complementary feeding at the age of 6-8 months (55.7%) were low. It showed that 90.4% of mothers have knowledge on exclusive breast feeding but only 57.3% of them have practiced it for 4-6 months. It further revealed that only 8.4% of mothers & 13.6 % of fathers are illiterate. The main problems revealed from the study were late initiation of breastfeeding, low rates of exclusive breastfeeding and inappropriate complementary feeding practices. It further revealed that 69.3% of the respondents had two or less children and only 30.7% had three or more children. Medicine Today 2016 Vol.28(1): 1-5